Avaliação da contaminação de córregos de Cerrado por metais pesados utilizando-se larvas de Odonata como bioindicadores - Bruno, Cyntia Goulart Corrêa (2012)
The aquatic ecosystems are the main receptors of pollutants and contaminants from industrial and agricultural activities and of the discharge of sewage. Among the various substances potentially harmful, heavy metals are a threat to the aquatic ecosystems and the biota. This research aimed to evaluate the contamination of Cerrado s streams by heavy metals using Odonata s larvae as bioindicators, by analyzing biological parameters and evaluating the concentration of metals in the sediments and in the larvae. Samples were collected between October 2010 and August 2011. For the fauna, the abundance of individuals, richness of taxa and the diversity index of Shannon- Wiener (H\') and Pielou\'s equity index (J\') were calculated. The presence of metals in the sediment and in the larvae was measured by atomic absorption spectrometry and atomic emission spectrometry with inductively coupled plasma, respectively. Cluster analysis was performed for the set of streams for the concentrations of Cu, Zn, Ni, Fe and Mn in sediments, and concentrations of Cu, Zn and Ni in the sediment were compared with a table of guide values. Canonical Redundancy Analysis (RDA) was performed to discriminate metals that contributed most to the variance of the biological parameters. Significance of heavy metals on the fauna of Odonata was evaluated by Canonical Correspondence Analysis (CCA). A Principal Component Analysis (PCA) was performed to determine the most important patterns in the concentrations of Cu, Zn, Fe and Mn in the larvae and in the sediments and the bioaccumulation factor (BAF) was calculated to assess the potential for bioaccumulation of metals by the larvae. The Cluster analysis promoted the formation of groups of streams due to the greater or lesser concentration of heavy metals in the sediment, which may have been influenced by the presence or absence of riparian vegetation and agricultural activities in the surrounding areas of the streams. The comparison with the table of guide values indicated that the streams which showed the highest concentrations of metals in the sediment were also those who had values above the limits given for at least one of the metals evaluated. The CCA indicated that most taxa of Odonata presented opposite distribution in relation to the vectors of heavy metals, while the family Libellulidae was abundant in streams subject to greater anthropogenic influence. There was low similarity between the distribution patterns of the PCA diagrams for the sediment and larvae, which indicates the importance of assessments not only in the sediment, but also in the organisms for the achievement of results more efficient about heavy metal contamination. The BAF showed a tendency to bioaccumulation of Zn and Mn by the Gomphidae larvae, indicating that these metals are able to concentrate on its bodies, reflecting the environmental conditions where these organisms live and thus serving as important tools in biomonitoring studies. The results of this study emphasize the potential of the order Odonata for environmental studies, because they demonstrated to be able to reflect the conditions of their environment with respect to the concentration of heavy metals.